Magnifying Focusing Events: Global Smoke Plumes and International Construal Connections in Newspaper Coverage of 2020 Wildfire Events - Groff, Stephen P. (Frontiers in Communication, 2021)
As climate policy focusing events, wildfires are distinct from hurricanes, floods, and tornados because they also result in the release of massive smoke plumes that contribute to the concentration of atmospheric carbon. However, unlike melting glaciers, wildfires may be easier to dismiss as individual acts of human error, spontaneous acts of mother nature, and/or necessary ecological processes of agricultural renewal. This paper presents a mixed-methods analysis of 150 international and domestic English language newspaper articles related to wildfire events occurring in Australia, Canada, Germany, Greece, Italy, Spain, the United Kingdom, and the United States during the year 2020. The analysis examines how news coverage of wildfire events might focus or diffuse attention to international climate policy and anthropogenic global warming. The quantitative findings provide evidence to suggest that 30% of wildfire coverage is attributed to climate change. However, qualitative analysis suggests that climate change is acknowledged as a blame frame that is often only inferentially attributed to anthropogenic origins. The mixed-methods analysis finds that only 6% of news coverage related wildfire events to emission contributions. The analysis of these exemplar articles suggests that the international travel of wildfire smoke may serve as a focusing event from which to emphasize wildfires as both a consequence of and contributor to, global warming. Findings indicate that environmental coalitions and scientific experts’ engagement with the press are integral to creating frames that link the increasing frequency, duration, and range of wildfire events to climate policy needs.